CONCEPT ANALYSIS OF MATERNAL-FETAL ATTACHMENT - Endang Koni Suryaningsih; Meei-Ling Gau; Wantonoro Wantonoro (Belitung Nursing Journal, 2020)
Background: Knowing about prenatal attachment is crucial because it plays a significant role in pregnant women and their babies' health. Healthcare providers, particularly midwives, need to understand the concept of attachment between mother and unborn baby. However, surrogate terms to apply the concept of maternal-fetal attachment are found, and ambiguity on the definition remains. Objective: To provide a more precise definition of the concept of maternal-fetal attachment Method: The Walker and Avant's concept analysis approach was applied. Results: The attributes of maternal-fetal attachment include (i) having a positive emotion, (ii) paying attention to the physical progress of the fetus and mothers themselves, (iii) having a reciprocal interaction with the baby, (iv) monitoring and imaging the unborn baby, and (v) having a desire to protect her unborn baby from harm and increase her health practices. Maternal-fetal attachment is the affection relationship, desire for protection, building the interaction, and the emotional tie between the mother and her unborn baby during the pregnancy. This personal connection is developed, mainly when the quickening is present during the late stage of pregnancy. Maternal-fetal attachment creates an emotional relationship with the unborn baby and leads the mother to express it with behavior. Conclusion: This concept analysis provides new insight into the maternal-fetal attachment concept used for nurses and midwives in their practice.